USM COMMUNITY ENCOURAGED TO APPLY FOR SOCIAL INNOVATION GRANTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
NIBONG TEBAL, PENANG, September 2015 All members of the Universiti Sains Malaysia (USM) community are encouraged to apply for grants on social innovation offered by the Ministry of Science, Technology and Innovation (MOSTI) in the realisation of products or innovations without research.